2009
DOI: 10.5424/sjar/2009074-1101
|View full text |Cite
|
Sign up to set email alerts
|

The use of correspondence analysis in the study of beef quality: a case study on Parda de Montaña breed

Abstract: The fulfilment of consumer needs is the main concern of the food industry. Sensory studies performed by both trained panellists and consumers play an important role in attaining this goal. Trained panel are required to detect small differences in food properties with accuracy and consistency, whereas the goal in consumer tests is to obtain information on consumer characteristics, attitudes and preferences. Consumer tests are classified according to the place where they are held. AbstractThe present study show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
1
0
1
Order By: Relevance
“…Again, this reveals the importance of sociodemographics in shaping consumer attitudes to certain foods. The observed gender effect (Table ) is consistent with findings obtained by Panea, Casasús, Blanco, and Joy (), Reicks et al () and Gracia, de Magistris, and Nayga (), and the observed age‐related variation in consumer preferences in this food category is reported in Panea et al () and Reicks et al (), who reported that males and younger interviewers prefer the more mature beef.…”
Section: Resultssupporting
confidence: 90%
“…Again, this reveals the importance of sociodemographics in shaping consumer attitudes to certain foods. The observed gender effect (Table ) is consistent with findings obtained by Panea, Casasús, Blanco, and Joy (), Reicks et al () and Gracia, de Magistris, and Nayga (), and the observed age‐related variation in consumer preferences in this food category is reported in Panea et al () and Reicks et al (), who reported that males and younger interviewers prefer the more mature beef.…”
Section: Resultssupporting
confidence: 90%
“…Consumers who reported liking meat very much penalized meat aged for 8 days and showed a clear preference for beef aged for 15 days. The overall appraisal was highly conditioned by tenderness, as reported by Panea et al, 37 but also by consumer characteristics.…”
Section: Consumer Sensory Testmentioning
confidence: 53%
“…Por otra parte, Bernués et al (2003b) u Olaizola et al (2005, obtuvieron como resultado que la raza se encuentra entre los atributos menos importantes, por lo tanto le asignarían menor relevancia que en nuestro estudio, y argumentan que esto puede ser motivado por la escasa información que recibe el consu midor sobre la raza del animal en el momen to de la compra. En nuestro caso, el grado de conocimiento de las distintas razas, y la asociación entre raza y calidad organoléptica por parte de los consumidores, podrían ser objeto de futuros estudios que completarían trabajos previos sobre aceptabilidad sensorial de la carne de razas específicas (Ripoll et al, 2014;Panea et al, 2009). La fecha y la edad de sacrificio tendrían una importancia media alta, al igual que en Mtimet et al (2013), mientras que la presencia de un color más rojo y de una etiqueta nutricional se podría considerar como media, siendo la recomendación del modo de cocinado, la existencia de ribete y vetas de grasa infiltrada, o de un precio más alto los menos influyentes.…”
Section: Calidad Percibida En El Momento De La Compra De Carne De Vacunounclassified